1994
DOI: 10.1902/jop.1994.65.9.881
|View full text |Cite
|
Sign up to set email alerts
|

Bone Grafting and Guided Bone Regeneration for Immediate Dental Implants in Humans

Abstract: This study evaluated bone regeneration and osseointegration of hydroxyapatite (HA) coated and titanium plasma sprayed (TPS) implants placed in sockets immediately after extraction in 36 adults, mean age 55.2 years (range 26 to 81 years). Twelve TPS and 10 HA‐coated implants in 20 patients were grafted with demineralized freeze‐dried bone allograft (DFDBA), covered with a barrier material, and the facial flap coronally positioned to attain primary closure (experimental). The remaining 11 TPS and 10 HAcoated imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
9

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(178 citation statements)
references
References 5 publications
7
160
0
9
Order By: Relevance
“…Gher et al (12) reportaron que para lograr regeneración en un defecto óseo, las tasa de osteogénesis, que se extiende desde los márgenes óseos adyacentes, debe ser superior a la tasa de fibrogénesis, proveniente de los tejidos blandos adyacentes.…”
Section: Regeneración óSea Guiada (Rog)unclassified
“…Gher et al (12) reportaron que para lograr regeneración en un defecto óseo, las tasa de osteogénesis, que se extiende desde los márgenes óseos adyacentes, debe ser superior a la tasa de fibrogénesis, proveniente de los tejidos blandos adyacentes.…”
Section: Regeneración óSea Guiada (Rog)unclassified
“…Grafts compensate for the bone resorption that accompanies the natural healing process in an extraction socket. [32][33][34][35] When implants are placed 8 to 16 weeks after tooth extraction, the clinician must compensate for the loss of labial bone that occurs during the early phase of extraction site healing. [36][37][38] To prevent the need for hard or soft tissue grafting when implant placement is delayed, it is recommended to place an osteoconductive graft material within the extraction site to promote bone fill, to limit labial bone collapse, and to maintain bone for optimal implant placement.…”
Section: Immediate Placement Of Implants At Tooth Extraction Indicatimentioning
confidence: 99%
“…Animal experiments (Gotfredsen et al 1993;Kohal et al 1999a) and clinical studies (Gher et al 1994;Simion et al1994;Hämmerle et al 1998) have shown that premature membrane exposure and wound dehiscence impair the amount of bone regeneration. Figure 4 presents the exposure and removal of an infected e-PTFE membrane.…”
Section: Tissue Barriersmentioning
confidence: 99%